2022
DOI: 10.22541/au.167048830.02473076/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transpiration drives diurnal and seasonal streamflow in secondary tropical montane forests of Eastern Himalaya

Abstract: Vegetation studies establishing direct mechanistic linkages between stand transpiration and streamflow are rare from sub-tropical and tropical montane forests (TMFs) like Himalaya. We quantified the impact of diurnal and seasonal transpiration on lean season streamflow in a broad-leaved evergreen secondary TMF in Eastern Himalaya. Whole-tree and stand transpiration were measured using Granier’s thermal dissipiation sap flow probes at one of the wettest (4500 mm yr-1) and highest elevation (2100 m) sites in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Soil moisture was both a limiting variable for pioneer species, as seen by the positive lags and negative autocorrelation coefficients, and a resource depleted by vegetation water use ( Fig. 4C , F ), something that particularly applies for the deep-rooted and large-sized individuals of Fagaceae (late-successional species) ( Kumar et al , 2022 , Preprint). Our results correspond to similar observations from Central Panama where older and large-sized late-successional species continue transpiring unperturbed even under drought conditions, while younger pioneer species reduce their water use ( Bretfeld et al , 2018 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Soil moisture was both a limiting variable for pioneer species, as seen by the positive lags and negative autocorrelation coefficients, and a resource depleted by vegetation water use ( Fig. 4C , F ), something that particularly applies for the deep-rooted and large-sized individuals of Fagaceae (late-successional species) ( Kumar et al , 2022 , Preprint). Our results correspond to similar observations from Central Panama where older and large-sized late-successional species continue transpiring unperturbed even under drought conditions, while younger pioneer species reduce their water use ( Bretfeld et al , 2018 ).…”
Section: Discussionmentioning
confidence: 97%
“…Similar reports from Central Himalayan species belonging to the Fagaceae , including Castanopsis indica , Quercus semicarpifolia , Q. leucotrichophora , and sub-canopy Rhododendron arboreum , have shown that seasonal soil moisture stress can induce a midday slump in leaf water potential ( Zobel et al , 2001 ; Poudyal et al , 2004 ; Tewari et al , 2018 ). The absence of significant midday depression in deep-rooted species such as C. hystrix at the peak of the dry season and strong diel cycles in soil moisture provide evidence of vegetation accessing moisture from deeper soil layers ( Tanaka et al , 2004 ; Allen, 2014 ; Kumar et al , 2022 , Preprint).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation